A comparative evaluation of market based measures for shipping decarbonization - Psaraftis, Harilaos N.; Zis, Thalis; Lagouvardou, Sotiria (My University, 2021)
The purpose of this paper is to provide an overview and discussion of potential Market Based Measures (MBMs) under the Initial IMO Strategy for the reduction of greenhouse gas (GHG) emissions from ships. In this context, some related developments are also seen as directly relevant, mainly in the context of the possible inclusion of shipping into the EU Emissions Trading System (ETS). A comparative evaluation of maritime MBMs is made using the following criteria: GHG reduction effectiveness, compatibility with existing legal framework, potential implementation timeline, potential impacts on States, administrative burden, practical feasibility, avoidance of split incentives between ship-owner and charterer, and commercial impacts. The paper breaks down potential MBMs into the following classes: Bunker levy/carbon levy MBMs, ETS (global and/or EU ETS) MBMs and other MBM proposals.
Keywords: IMO; Decarbonization; Greenhouse gases; Market Based Measures